Avaliação da fala e da linguagem perspectivas interdisciplinares em Fonoaudiologia - Giacheti, Célia Maria (Editora Oficina Universitária, 2020)
This book is the result of the scientific activities developed during the III International Symposium of the Research Group "Speech and Language Assessment" - Interdisciplinary Perspective in Speech Therapy; II Meeting of Researchers in Language; and III Brazilian Congress of Speech Therapy and Genetics of Communication Disorders. This event was held from May 16 to 18, 2019, at the Universidade Estadual Paulista Júlio de Mesquita Filho - UNESP, in the municipality of Marília - SP, under my coordination. The Symposium aimed to promote a debate on contemporary themes in Speech and Language Assessment and the intersection of large areas of knowledge, which share the same research object - Human Communication and its disorders.